Arabic Language Learning Media Based on Technology from the Perspective of the Qur'an - Sundirah Sundirah; Abdillah Rofiif Fatih Ritonga; Muhammad Hakim Parta; Rizqiqa Aulia Maharani (Journal of Arabic Literature, Teaching and Learning, 2026)
The development of digital technology has brought many changes to the world of education, including in Arabic language learning. However, many studies only highlight the technical and pedagogical aspects without considering the philosophical foundations and values ​​of the Qur'an. This article aims to analyze the concept of technology-based Arabic language learning media from the perspective of QS. Al-'Alaq verses 1-5 as the religious basis and norms in the development of such media. This study uses a qualitative method with a library research approach and analysis of the interpretation of as-Tsaqafiy to examine the meaning of the verses textually, historically, and contextually. The results of the study indicate that QS. Al-Alaq verses 1-5 contain the main principles of learning, namely monotheism as the foundation of learning, gradual progressive learning, the use of media as a means of knowledge, and lifelong learning. The integration of these values ​​provides a new direction for the development of technology-based Arabic language learning media that are not only pedagogically effective but also spiritually and morally meaningful. Thus, educational technology can be a means of actualizing divine values ​​in the Arabic language teaching and learning process.